2002
DOI: 10.1034/j.1600-0706.2002.960103.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of time‐dependent competition for oviposition sites on clutch sizes and offspring sex ratios in a fig wasp

Abstract: T. 2002. Effects of time-dependent competition for oviposition sites on clutch sizes and offspring sex ratios in a fig wasp. -Oikos 96: 31 -35.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
71
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(75 citation statements)
references
References 22 publications
(31 reference statements)
4
71
0
Order By: Relevance
“…We observed that each increase of one foundress produced broods seven to 13% larger than the previous one. If sequential oviposition takes place, as reported in the literature (Kinoshita et al, 2002;Moore et al, 2002), the second foundress probably contributes with a smaller proportion of eggs to the total brood. The weak adjustment between the number of foundresses and total brood size (R 2 = 0.1, Fig.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…We observed that each increase of one foundress produced broods seven to 13% larger than the previous one. If sequential oviposition takes place, as reported in the literature (Kinoshita et al, 2002;Moore et al, 2002), the second foundress probably contributes with a smaller proportion of eggs to the total brood. The weak adjustment between the number of foundresses and total brood size (R 2 = 0.1, Fig.…”
Section: Discussionmentioning
confidence: 65%
“…[603][604][605][606][607][608][609][610]2006 such a condition, first-arriving foundresses laid large female-biased clutches, contributing to more female-biased sex ratios. If P. tonduzi behaves like other fig wasp species [e.g., Liporrhopalum tentacularis (Moore et al, 2002) and Blastophaga nipponica (Kinoshita et al, 2002)], foundresses that arrive later will lay small less female-biased clutches, by facultatively adjusting their brood sex ratios according to the LMC level or by laying the males at the start of an oviposition bout (Kinoshita et Moore et al, 2002). The positive correlation between the P. tonduzi sex ratio and the brood size supports this hypothesis.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These arguments receive support from B. nipponica: foundresses are less oviposition site limited in multifoundress figs than in L. tentacularis (Kinoshita et al 2002). The findings presented here, though, indicate another factor likely to affect cue use patterns.…”
mentioning
confidence: 49%
“…Hence, to maintain the optimal sex ratio as clutch size increases, they should produce mostly male offspring at the start of oviposition bouts, followed by mostly females with a few males interspersed (see also Stubblefield & Seger 1990). However, clutch and brood sex ratios similar to those observed could also be as a consequence of another strategy, that of depositing a number of males at the beginning of oviposition bouts followed by only females (see also Herre et al 1997;Kinoshita et al 2002;Moore et al 2002;Kjellberg et al 2005). To determine whether foundresses use clutch size as a cue or pursue a 'males first' strategy, we quantify the sequence in which they deposit male and female offspring by using insecticide to terminate oviposition bouts at varying times after entry to the fig.…”
Section: Introductionmentioning
confidence: 61%